Effect of manufacturing and protein level in diets with corn and soybean on performance of weaned piglets - Neto, Messias Alves da Trindade; Barbosa, Hacy Pinto; Petelincar, Izabel Marin; Schammass, Eliana Aparecida (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this study was to evaluate diets with corn and soybean manufactured with different processes and protein levels on weaned piglets performance. Two experiments were carried out, each one with 80 piglets weaned when they were 20 and 18 day-old, in the first and second experiments, respectively. The experiments were in a randomized block design in a 2x2 factorial scheme, with five replications and four animals per experimental unit. Daily records of weight gain, food ingestion and food conversion were made in piglets in three phases of development, according to piglets age, in both experiments. Treatments of the first experiment used two manufacturing processes in corn (common and pre-cooking) and in soybean (meal and macerated full fat); the second experiment consisted of diets with pre-cooking corn and macerated full fat soybean, containing or not milk by-products and 18% and 15% protein level. In the first experiment, common corn and soybean meal allowed better performance of piglets in all phases. In the second experiment, milk by-product diets showed the best results, in all phases, and the 18% crude protein allowed higher piglets performance on the first phase.